Design Thinking dalam Inovasi Layanan Hewan Peliharaan: Studi Pengembangan Aplikasi UnityPet - Sukmasetya, Pristi; Nuryanto; Widodo, Eko Muh (TeIKa, 2024)
This study aims to design and develop UnityPet, an integrated application for pet owners and professionals in the pet industry, using the Design Thinking methodology. The application is designed to address specific user needs by providing various services, including online veterinary consultations, grooming services, pet sitting, an online store for pet supplies, and interactive features for communication between users and professionals. The research process includes five key stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test. The Empathize stage identifies primary challenges faced by users, such as the difficulty in finding a comprehensive platform for pet-related services and communication barriers with professionals. The Define stage formulates the core user problems as a foundation for ideation, where various application features are developed according to these needs. In the Prototype stage, wireframes and interactive prototypes are created to visualize and test the application’s functionality. Finally, usability testing is conducted in the Test phase to assess the application’s effectiveness, efficiency, accuracy, and user-friendliness. The testing results indicate an effectiveness rate of 84%, with efficiency, accuracy, and user-friendliness scores reaching 92%, surpassing the acceptance threshold of 75%. These findings demonstrate that UnityPet is not only functional but also offers an intuitive and satisfying user experience. UnityPet successfully meets usability standards and is ready for implementation, promising a positive contribution to the pet care industry